Probing Temperature Dependent Noise in Flux Qubits via Macroscopic Resonant Tunneling; Bulletin of the American Physical Society; Vol. 53, № 2 - Berkley A. J.; Harris R.; Johnson M. W.; Johansson J.; Bunyk P.; Govorkov S.; Thom M. C.; Uchaykin (Uchaikin) S. V. Sergey Victorovich; Truncik C. J. S.; Amin M. H. S.; Han S.; Bumble B.; et al. (2008, 2008)
Macroscopic resonant tunneling between the two lowest lying states of a bistable RF-SQUID is used to characterize flux noise in a potential qubit. Detailed measurements of incoherent decay rates as a function of flux bias revealed that the Gaussian shaped tunneling rate is not peaked at the resonance point, but is shifted to a flux bias at which the initial well is higher than the target well. This observation indicates that the dominant low frequency (1/f) flux noise in this device is quantum mechanical in nature. The r.m.s. amplitude of the noise, which is proportional to decoherence rate 1/T ∗ 2 , was observed to be weakly dependent on temperature below 70 mK.